Evaluation of the Efficiency and Stability of High-Frequency Inverters Under Varying Load Profiles in Photovoltaic Systems - Zahro, Nabila Aida Az; Samaratungga, Langga; Hendrawati, Dwiana; Ferandez, Aggie Brenda; Efendi, Erwan Tri (Eksergi, 2025)
This research undertakes an operational performance analysis of a high-frequency inverter (HFI) within a Solar Power Plant (SPP) system configuration. The investigation prioritizes assessing the effects of pure resistive and mixed resistive-inductive load profiles on its efficiency stability. Experimental findings definitively demonstrate that the HFI inherently maintains superior efficiency stability when operating under purely resistive loads. Conversely, the introduction of varying inductive loads tends to compromise this efficiency stability, inducing significant fluctuations. These results yield crucial recommendations, establishing that HFIs are optimally suited for systems with predominantly resistive loads, thereby contributing to the overall system power efficiency enhancement